Winter Population Size Estimations of Three Migratory Sheldgeese in the Southern Pampas, Argentina - Pedrana, Julieta (2018)
Sheldgeese [Upland Goose (Chloephaga picta picta), Ashy-headed Goose (C. poliocephala) and Ruddyheaded Goose (C. rubidiceps)] have similar migratory patterns, breeding in Patagonia (Argentina and Chile) and wintering mainly in the southern Pampas, Argentina. All of them are species of conservation concern in Argentina. The objective of this study was to estimate species densities using distance sampling and to calculate population sizes over three categories of habitat quality in the southeast of Buenos Aires Province, Argentina. Road surveys (9,200 km) were performed from a vehicle during two consecutive wintering seasons (13 June to 6 July 2011 and 9 June to 4 July 2012). Predicted probabilities of sheldgeese occurrence were divided into three classes of habitat quality. Upland Goose mean density was estimated at 3.72 individuals/km2, Ashy-headed Goose at 1.62 individuals/km2 and Ruddy-headed Goose at 0.04 individuals/km2. Consequently, Upland Goose numbers were estimated at 348,255 individuals, Ashy-headed Goose at 151,803 individuals and Ruddy-headed Goose at 498 individuals in the southeast of Buenos Aires Province. The results confirm former studies regarding the small population sizes of these species in comparison with historic data and suggest a decline in sheldgeese populations.